Over-Expression of Chorismate Mutase Enhances the Accumulation of Salicylic Acid, Lignin, and Antioxidants in Response to the White-Backed Planthopper in Rice Plants - Rahmatullah Jan; Muhammad Aaqil Khan; Sajjad Asaf; Lubna; In-Jung Lee; Kyung-Min Kim (MDPI AG, 2021)
The white-backed planthopper (WBPH) is a serious pest of rice crop and causes sever yield loss each year, especially in Asian countries. In this study, we used chorismate mutase (CM) transgenic line to examine the defense mechanism of rice plants against WBPH. The survival rate of WBPHs, infestation rate of plants, lignin biosynthesis, transcriptional regulation of related genes, salicylic acid (SA) accumulation and signaling and antioxidants regulation were investigated. The WBPH population decreased by 67% in OxCM-t, and the plant infestation rate was 3.5-fold higher in wild-type plants compared with transgenic plants. A substantial increase in lignin was found in the transgenic line (742%) and wild-type (417%) plants. Additionally, CM, phenylalanine ammonia lyase (PAL), chalcone synthase (CHS), and chalcone isomerase (CHI) showed significant increases in their relative expression level in the transgenic line. Salicylic acid was significantly enhanced in the transgenic line compared with WBPH infestation. SA can activate pathogenesis related proteins-1 (PR1), PR2, antioxidants, and the expression of their related genes: superoxide dismutase (SOD) and catalase (CAT). WBPH infestation reduced the chlorophyll contents of both transgenic and wild-type plants, but the reduction was great in wild-type than transgenic plants. The sugar content was only significantly increased in the transgenic line, indicating that sugars are not heavily involved in WBPH stress. Phenylalanine, proline, aspartic acid, and total amino acids were increased in the transgenic line and reduced in the wild-type plants. Taken together, all the results suggest that overexpression of CM gene regulates the defense mechanisms and enhances the rice toward WBPH stress.